Does Herding Occur During the Presidential Election in the Indonesian Capital Market in 2024? - Erlangga, M. Sandi Surya; Hikmah, Khoirul; Ambarwati, Sri Dwi Ari (CV. Strata Persada Academia, 2024)
Amid the uncertainty of the presidential election, investors' emotions, beliefs, and perceptions are affected, resulting in behavioral biases in decision making such as herding behavior. This study aims to determine whether the 2024 Presidential Election has an effect on the herding behavior of investors in the Indonesian capital market. By looking at the relationship between Cross Sectional Absolute Deviation (CSAD) and market returns 1 month before and after the presidential election, herding behavior in the stock market can be determined. The population in this study are companies listed on the LQ45 index in 2024 and uses the purposive sampling technique and there are 35 companies will then be used as samples in this study. This study uses quantile regression analysis because herding detection is carried out in different market conditions in which these conditions are normal market, stress market and high returns market. The results of this study indicate that the presidential election has an effect on the herding behavior of investors in the Indonesian stock market, both before and after the presidential election.